HUBUNGAN PERSEPSI WANITA USIA SUBUR (WUS) TENTANG KANKER SERVIKS DENGAN MOTIVASI PEMERIKSAAN PAP SMEAR DI DUSUN SAPUANGIN KELURAHAN SRANDAKAN KABUPATEN BANTUL YOGYAKARTA - Bustanil Bustanil; Dina Putri Utami Lubis (STIKES Wira Husada Yogyakarta, 2018)
Background: Cervical cancer is cancer that often happens and that causes of death to women. More than 270,000 deaths of cervical cancer each year in developing countries (WHO, 2014). Objective: To determine the correlation of perception of women in reproductive about cervical cancer with motivation Pap smear in Sapuangin, Srandakan, Bantul, Yogyakarta.Methods: Research methods is used in my research was quantitative research using a descriptive correlation design with cross sectional approach. The population women in reproductive age with the number 46 of sons in Sapuangin, Srandakan, Bantul, Yogyakarta. Sampling technique using saturated purposive sampling. Data collection using the questionnaire. Data analyzed used univariat analysis by ﬁ nding the frequency distribution and bivariate analysis by correlation perception of women in reproductive age about cervical cancer with motivation Pap smear by Chi-Square. Results: Statistical test results obtained using the Chi-Square X 2 result amounted to 13.295> 5.591 X 2 tabel, the value of ρ value of 0,001 (ρ <0.05) and showed that Ha Ho accepted and rejected, meaning there is a perception of women in reproductive age about cervical cancer with motivation Pap smear in sapuangin. 0495 correlation value and signiﬁ cance value of 0.001.Conclusion: There is a relation perception of women in reproductive age about cervical cancer with motivation Pap smear in Sapuangin, Srandakan, Bantul, Yogyakarta